UNVEILING OF GENERATION Z’S INTENTION TO ADOPT E-MONEY AMID PAYMENT DIGITALIZATION: EVIDENCE FROM HIGHER EDUCATION STUDENTS - Satria Abadi; Mohd Hishamuddin bin Abdul Rahman; Febriansyah Febriansyah; Febby Angelia (YHMM PUBLISHING, 2026)
The rapid digitalization of payments has propelled e-money adoption, yet Generation Z’s (Gen Z) intentions remain underexplored, particularly among higher-education students in Indonesia. This study aims to investigate several factors affecting the behavioral intentions of Generation Z in Indonesian higher education institutions' use of e-money payment. The study extended the Technology Acceptance Model (TAM) integrated with the Technology-Organization-Environment (TOE) framework. Using a quantitative approach, we surveyed 300 students from public and private universities in Indonesia, analyzing data via Structural Equation Modeling-Partial Least Squares (SEM-PLS). Findings reveal that perceived usefulness, perceived ease of use, digital literacy, and social factors significantly influence adoption intentions amid digital payment ecosystem challenges. These insights offer practical implications for e-money providers, policymakers, and educators in fostering digital entrepreneurship among Gen Z, contributing to Indonesia's cashless society agenda and MSME competitiveness in fintech-driven markets.